1989
DOI: 10.1111/j.1365-2044.1989.tb11234.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Pharmaseal continuous flushing device

Abstract: SummaryPharmaseal continuous flushing devices were tested with regard to flow characteristics into simulated arterial and venous pressure systems. Two driving pressures were used and it was found that variation in driving pressure made a significant difference to the flow, while arterial or venous pressure made no signgcant difference. The $ow devices had a wide variation although they were all of the same type. The fluid volume delivered was in the region of 100 ml in a 24-hour period,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In radial and femoral arterial catheters, fast bolus flushing is commonly performed by means of a flow regulating device integrated into the pressure transducer. [11][12][13] Among the many events associated with arterial catheterization, retrograde embolization into the central arterial circulation from flushing the arterial cannula carries a substantial risk, particularly in small patients. Retrograde embolization of clots into the central arterial circulation causing cerebrovascular accidents in adults was first described by Gaan et al 14 Lowenstein et al found a high correlation between patient height, minimum volume of flush solution and cerebral embolization.…”
Section: Me Et Th Ho Od Ds S:mentioning
confidence: 99%
See 1 more Smart Citation
“…In radial and femoral arterial catheters, fast bolus flushing is commonly performed by means of a flow regulating device integrated into the pressure transducer. [11][12][13] Among the many events associated with arterial catheterization, retrograde embolization into the central arterial circulation from flushing the arterial cannula carries a substantial risk, particularly in small patients. Retrograde embolization of clots into the central arterial circulation causing cerebrovascular accidents in adults was first described by Gaan et al 14 Lowenstein et al found a high correlation between patient height, minimum volume of flush solution and cerebral embolization.…”
Section: Me Et Th Ho Od Ds S:mentioning
confidence: 99%
“…Design and function of such flow regulating devices are described in detail by Latimer and Latimer and McKinney and Orr. 4,12 Syringe pump flush systems are the standard for neonates and small children. They allow continuous low flow rates of 0.5-1 mL·hr -1 and the use of measured flush boluses.…”
Section: Measurementsmentioning
confidence: 99%
“…In bag pump flush systems a 250-to 500-ml plastic bag filled with heparinized solution is compressed by a bag pump at pressures of up to 300 mmHg. Combined with a standard flow regulating device, a continuous flow of about 3 ml/h is delivered through the arterial cannula [5]. Manual release (opening) of the flow regulating device allows rapid flushing for purging of the line and cannula from blood and clots, particularly after blood sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Pressurized bag pump flush systems usually require a 250-500 ml plastic bag of a heparinized solution compressed by a bag pump up to 300 mmHg 3,4 . In combination with a standard flow-regulating device a continuous flow of approximately 3 ml/h is delivered through the arterial cannula 5 . Opening the flowregulating device also allows fast bolus flushing in order to purge the pressure monitoring line and cannula of blood.…”
mentioning
confidence: 99%
“…Different authors have reported on the variability of fluid rates at 300 mmHg manometer pressure through flow-regulating devices of the same brand (range 3.1 to 4.6 ml/h) and among different models of flow-regulating devices (range 2.6 to 5.7 ml/h) 5,6,7 . Hart and co-workers demonstrated considerable differences between manometer pressure and delivered infusion pressure with decreasing fluid bag volume leading to decreased flow rate through the flowregulating device 7 .…”
mentioning
confidence: 99%